2020
DOI: 10.1186/s13073-020-00750-5
|View full text |Cite
|
Sign up to set email alerts
|

cfNOMe — A single assay for comprehensive epigenetic analyses of cell-free DNA

Abstract: Cell-free DNA (cfDNA) analysis has become essential in cancer diagnostics and prenatal testing. We present cfNOMe, a two-in-one method of measuring cfDNA cytosine methylation and nucleosome occupancy in a single assay using non-disruptive enzymatic cytosine conversion and a custom bioinformatic pipeline. We show that enzymatic cytosine conversion better preserves cfDNA fragmentation information than does bisulfite conversion. Whereas previously separate experiments were required to study either epigenetic mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 38 publications
2
49
0
Order By: Relevance
“…In-house analysis of numerous cfDNA samples using TapeStation has shown that the majority of cfDNA fragments are indeed within the 50–200 bp range (with the median being ~167 bp, associating cfDNA with mononucleosomes [ 41 ]), showing, again, that contamination with germline DNA is minimalized (expected range for germline DNA is >10,000 bp). This has also been shown by others [ 42 , 43 , 44 ], confirming that robust pre-analytical handling of blood samples is a critical factor in cfDNA analysis [ 19 , 36 , 45 ]. Germline DNA was extracted from 200 μL of buffy coat using the QIAamp DNA Blood Mini kit (Qiagen), according to manufacturer’s instructions.…”
Section: Methodssupporting
confidence: 82%
“…In-house analysis of numerous cfDNA samples using TapeStation has shown that the majority of cfDNA fragments are indeed within the 50–200 bp range (with the median being ~167 bp, associating cfDNA with mononucleosomes [ 41 ]), showing, again, that contamination with germline DNA is minimalized (expected range for germline DNA is >10,000 bp). This has also been shown by others [ 42 , 43 , 44 ], confirming that robust pre-analytical handling of blood samples is a critical factor in cfDNA analysis [ 19 , 36 , 45 ]. Germline DNA was extracted from 200 μL of buffy coat using the QIAamp DNA Blood Mini kit (Qiagen), according to manufacturer’s instructions.…”
Section: Methodssupporting
confidence: 82%
“…TAPS and EM-Seq are sequencing methods based on enzymatic conversion of DNA (see previous section). EM-Seq has been used to develop cfNOMe (cell-free DNA-based nucleosome occupancy and methylation profiling), a single assay to evaluate the methylation status and nucleosome position on cfDNA from plasma and urine samples [ 63 ]. TAPS has also been successfully applied for cfDNA analysis [ 50 ].…”
Section: Experimental Assays For Dnam Evaluationmentioning
confidence: 99%
“…Lampignano et al suggested that downstream analytical processes, such as massively parallel sequencing (MPS) and droplet digital PCR, could be utilized with a variety of collection tubes [ 161 ], however, there are some exceptions, usually when methylation analyzes should be performed. For example the Streck Cell-Free DNA BCT tubes do not seem to work for such analyzes, therefore the use of the Qiagen PAXgene Blood ccfDNA Tubes should be considered when designing methylation assays [ 106 ], however, there are also reports of the use of the Streck Cell-Free DNA BCT tubes for epigenetic analysis of cfDNA [ 162 ]. Although K 2 EDTA showed worse effect then the Streck Cell-Free DNA BCT tubes on the cfDNA and ctDNA recovery, it seems that on the quality of MPS analyzes neither of these preservatives have noticeable effect [ 26 ], even the Streck Cell-Free DNA BCT tubes can be used for the library preparation for aneuploidy detection in prenatal care without any unwanted changes [ 93 ].…”
Section: Sample Collectionmentioning
confidence: 99%
“…Using a microarray technology approximately 3000 different mRNAs were discovered in cell-free saliva. It points to that not only from blood, but cfNAs originating from all body fluids should be acquired in sufficient quality and quantity for plenty of downstream analysis regardless of whether they are performed in a diagnostic manner or in research [ 162 , 163 ].…”
Section: Sample Collectionmentioning
confidence: 99%